A CONVENIENT SYNTHESIS OF 1,3-DISILACYCLOBUTANES - HONG, JH; HAN, JS; LEE, GH; JUNG, IN (ELSEVIER SCIENCE SA LAUSANNE, 1992)
Flash vacuum pyrolysis of bis(trimethylsilylmethyl)methoxysilanes was found to be an efficient route to 1,3-disilacyclobutanes. Flash vacuum pyrolysis of bis(trimethylsilylmethyl)dimethoxysilane or bis(trimethylsilylmethyl)chloromethoxysilane gave 1-methoxy-1,3,3-trimethyl-1,3-disilacyclobutane or 1-chloro-1,3,3-trimethyl-1,3-disilacyclobutane, respectively. The thermolysis is regarded as proceeding through initial beta-elimination of trimethylmethoxysilane followed by intramolecular cyclization of the resulting 2-methoxy-4,4-dimethyl-2,4-disilapent-1-ene or 2-chloro-4,4-dimethyl-2,4-disilapent-1-ene to give the products.